Digital Literacy, Tax Knowledge, and MSME Tax Compliance in the Era of Digital Taxation - Adellya, Sherly; Markhumah, Umatun (Inovasi Analisis Data, 2026)
Purpose: The study tests the role of digital literacy and tax knowledge as antecedents to MSME tax compliance in digitally mediated taxation systems, integrating a conceptual divide in previous research. Method: A thematic and structural analysis of the literature: Digital tax compliance studies Contributing to digital tax research, SLR proponents an analysis based on both thematic synthesis and bibliometric mapping to (1) provide a broad scope depiction by synthesizing empirical evidence, and (2) create insights into structural patterns. Findings: The findings also show that digital literacy and tax knowledge positively influence on MSMEs tax compliance, but the relations are interdependent instead of independent. Digital literacy help the taxpayer in using electronic tax systems to reduce procedural complexities and operational mistakes and tax knowledge supports them in correct interpretation of tax rules. Enhancements in compliance are particularly significant when both these features present, which can account for the mixed results associated with digital tax reform reported in the literature. This bibliometric analysis shows a nascent move to capability-based theories of compliance and continued dichotomy between technical and cognitive viewpoints. Novelty: This paper contributes to tax compliance literature by theorising digital literacy and tax knowledge as complementary competences which interact to shape compliance conduct in digital taxation contexts. Implications: The results imply that digital tax reforms should be introduced as capacity-building programs, incorporating the enhancement of digital skills and adaptive tax education for inclusive and sustainable MSME tax compliance.